Effect of Weight-Loss Diet Combined with Taurine Supplementation on Fasting Levels of Fibroblast Growth Factors19, 21, and 𝛃-klothoCo-Receptor in Obese Women: A Randomized Clinical Trial - Maryam Asadi; Fatemeh Haidari; Hossein Bavi Behbahani; Maryam J Chitsazi; Javad Mohammadi-asl; Kambiz Ahmadi-Angali (Journal of Nutrition and Food Security)
Background: Taurine (Tau) is naturally synthesized in the body from cysteine. It plays a crucial role in lipid and carbohydrate metabolism, increasing energy consumption, reducing inflammation, and controlling appetite. Some research suggests that obesity may be associated with decreased serum Tau levels. This study is the first randomized controlled trial to assess the effectiveness of a Tau supplement in combination with a weight loss intervention on fibroblast growth factors (FGF) 19, 21, and β-Klotho co-receptor in obese women. Methods: Participants were randomly assigned to two groups: a standard weight-loss group receiving 3 g/day of Tau capsules for 8 weeks (n=20) and a standard weight-loss group receiving placebo capsules for 8 weeks (n=18). The weight loss intervention aimed to reduce 30% of the total energy consumed by the participants.A paired t-test and an independent sample t-test were employed to assess parametric continuous data within and between the groups. Analysis of covariance was utilized to control for confounding variables. Results: At post-intervention, there was a significant reduction in mean changes of β-Klotho (P=0.01) in Tau group, compared to the control group. However, there were no significant differences in mean changes of FGF 19 and FGF 21 between the two groups (P>0.05). Conclusion:This study suggests that Tau supplementation alongside a weight loss diet may lead to a reduction in serum levels ofβ-Klothoco-receptor, which could serve as an alternative marker of obesity.